Pelatihan Penggunaan Edmodo untuk Meningkatkan Pengetahuan Teknologi Pembelajaran Guru SMP Yapis Merauke - A Reski; I D Palittin (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
Changes in learning patterns from face-to-face to distance learning indirectly make teachers have to be able to adapt quickly to the use of technology as the main means of learning. The technological knowledge possessed by teachers is of course a major factor in the success and effectiveness of online learning. Community Service Activities carried out at the Yapis Merauke Junior High School aim to improve the ability of teachers to manage technology-based learning which is carried out in 3 forms of activity, namely socialization, training, and mentoring equipped with practice and learning simulations using Edmodo. The stages of activity include socializing about Edmodo as an e-learning platform, training on account creation and classes in Edmodo to assisting the use of Edmodo in learning activities, and evaluating activities to determine the increase in technological knowledge of Yapis Merauke Middle School teachers. The indicator of increasing technological knowledge is indicated by more than 75% of Yapis Junior High School teachers being able to use Edmodo as an online learning tool.